Comparison of Doppler Ultrasound and CT Angiography for Evaluation of Renal Artery Stenosis - Asif, Bilal; Abid, Hamna; Ahmed, Aliya; Suhail, Maham; Hussain, Shahid (Indus Journal of Bioscience Research, 2025)
Background: Renal artery stenosis (RAS) is an important cause of secondary hypertension and progressive renal impairment. Accurate and timely diagnosis is essential for appropriate management. This study aimed to compare the diagnostic performance of Doppler ultrasound with CT angiography and to identify clinical predictors of RAS. Methods: A cross-sectional study was conducted on 120 patients with suspected RAS. Demographic, clinical, and laboratory data were collected. All participants underwent Doppler ultrasound and CT angiography. Diagnostic performance metrics of Doppler ultrasound, including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy, were calculated using CT angiography as the reference standard. Multivariable logistic regression was performed to determine independent predictors of RAS. Clinical outcomes, including blood pressure control, renal function, and management strategies, were assessed at 6 months. Results: The study population had a mean age of 52.3 ± 9.6 years, with 60% males. Doppler ultrasound demonstrated a sensitivity of 79.4% (95% CI: 67.9–88.3), specificity of 84.6% (95% CI: 71.9–93.1), PPV of 87.1% (95% CI: 76.1–94.3), NPV of 75.9% (95% CI: 62.8–86.1), and overall accuracy of 81.7% (95% CI: 73.6–88.1). Multivariable analysis identified age ≥50 years (AOR 1.86, p = 0.041), hypertension duration >10 years (AOR 2.21, p = 0.013), current smoking (AOR 2.03, p = 0.028), eGFR